Correlation Study of Antioxidant Activity with Phenolic and Flavonoid Compounds in 12 Indonesian Indigenous Herbs - Yeni Maulidah Muflihah; Ganesh Gollavelli; Yong-Chien Ling (MDPI AG, 2021)
The antioxidant activity (AA), total phenolic content (TPC), and total flavonoid content (TFC) of selected Indonesian Zingiberaceae herbs were determined. An optimization extraction procedure was conducted by using Taguchi L16 orthogonal array. Four chemical assays were applied, including 2,2-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity assay, H2O2 scavenging activity assay, Folin-Ciocalteau (F-C) assay, and NaNO2-AlCl3-NaOH assay, which revealed remarkable differences in AA, TPC, and TFC. The result indicated the diversity of AA composition among the herbs, and C. longa exhibited the highest AA. HPLC-PAD analysis revealed that curcumin was present in five high antioxidant herbs, and the highest amount was in C. longa. Pearson correlation analysis indicated that the identified TPC and TFC were significant contributors to AA, and curcumin was likely the main contributing antioxidant compound. Our approach concluded that C. longa is the greatest source of natural antioxidants among 12 Indonesian indigenous Zingiberaceae herbs. The use of a mixed-method approach to augment the findings of solitary methods might facilitate future researchers to uncover deeper and hidden meanings.